Kedudukan Bapa Rohani dalam Penggembalaan Generasi Digital menurut 1 Korintus 4:14-21 - Joni Manumpak Parulian Gultom; Selvyen Sophia (Sekolah Tinggi Teologi Baptis, Jakarta, 2022)
Special attention was paid to the church as a New Testament divine institution with a pastor's role as a spiritual father who was the key in shepherding the digital generation to find an entire Christian life. It did not happen because of discontinuity in functions such as motivational factors, world pressures, and the wrong mentality of the shepherd. They should be maximized the part of the shepherd as a spiritual father in the digital era. The question was, what is the role and function of the spiritual father according to Paul in 1 Corinthians 4:14-21? And what is the strategy for developing the quality of spiritual fathers in existing pastoral leadership? The purpose of this study is [1] to explain the role and function of spiritual fathers as spiritual fathers referred to by Paul in 1 Corinthians 4:14-21, [2] to define strategies in developing the quality of spiritual fathers in maximum shepherding. This study concludes that the role and function of spiritual fathers in the digital era is [1] Disciplining and teaching the digital generation as loved children (v14). [2] Gospel-centered ministry is a key in character building (v15). [3] The spiritual father has the maximum life in exemplary (v16). [4] Creating and preparing new leaders from the digital generation to the future (v17).